Meningkatkan Minat dan Hasil Belajar IPS Melalui Penggunaan Media Pembelajaran Berbasis Wordwall pada Murid Kelas VI UPTD SDN 88 Barru Kecamatan Tanete Riaja Kabupaten Barru - Asridah, Asridah; W, Muhammad Fahreza; Nurdin, Nurdin (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This study aims to increase interest in social studies learning through the use of Wordwall-based learning media in grade VI students of UPTD SDN 88 Barru, Tanete Riaja District, Barru Regency and improve social studies learning outcomes through the use of Wordwall-based learning media in grade VI students of UPTD SDN 88 Barru, Tanete Riaja District, Barru Regency. The research method used is classroom action research The subject of this research is a student of class VI UPTD SDN 88 Barru, Tanete Riaja District, Barru Regency with a total of 16 students, consisting of 8 boys and 8 girls. This research was carried out in two cycles, namely cycle I which was carried out 3 meetings (the first and second meetings for the learning process and the third meeting for social studies learning outcome assessment activities) and cycle II was also carried out 3 meetings. The two cycles were carried out for 2 months plus summarizing all existing research results.  The results of the study show that the use of Wordwall-based learning media can increase students' interest in learning social studies in class VI UPTD SDN 88 Barru. This is evidenced by the increase in the average percentage of student learning interest indicators in each cycle. In the first cycle, the average percentage of student learning interest indicators was 57%. In the second cycle, there was a significant increase, namely by 26% to 83%. This means that the average percentage of student learning interest indicators has exceeded the set success criterion of 75%. The use of Wordwall-based learning media can improve student learning outcomes. This is evidenced by the percentage of students who achieved KKM scores in the first cycle of 31%, increasing to 94% in the second cycle. This means that the number of students who have achieved the KKM score (70) has exceeded the set success criterion of 75%.